En gammelkretisk gåde - Jeppesen, Kristian (Kuml, 1962)
Some Remarks on the Archeological Placing of the Phaistos Disc During the excavation of the Old-Cretan palace in Phaistos the Italian excavators uncovered in 1908 a remarkable clay disc, which has since been the subject of much scientific discussion (Pl. IV-V). The circular disc bears on both sides a spiral inscription, and numberless attempts have been made to decipher these texts, which each consist of about 30 words. But as the phonetic values to be given to the signs are still only a matter of guesswork the possibilities appear endless. The hieroglyphs of the disc resemble to some degree the local Cretan hieroglyphic script and the syllabic scripts A and B derived from it, and there is therefore a logical idea behind the attempt by Benjamin Schwartz, on a basis of the frequency of occurrence of each individual sign both on the disc and in the now deciphered Linear B script, to establish the phonetic value of the hieroglyphs 1). But the result of this statistical experiment, an attempt to translate the Phaistos Disc, produces no obviously coherent meaning, and would at best only appear to succeed in proving that the language of the disc cannot by Mycenean. After this negative result no other inviting linguistic channels present themselves 2), and it would appear best to concentrate on such questions as give a possibility of a result independent of guesswork. Among these are that of the disc's provenance and date, and general cultural historical context. If the literature concerning the Phaistos Disc be viewed as a whole it may be said that only a small minority of writers believe in a Cretan origin, and that the majority are of the opinion that the disc was imported into Crete and probably fashioned in Southwestern Asia Minor. Concerning the date there appears to be unanimity. In the absence of other criteria the circumstances of discovery are taken as decisive, and the disc attributed to MM III b, i. e. to the latter half of the 17th Century BC. Comparative material of a stylistic nature is not available, as the disc is unique, and only a very small number of details may be related to features of well-defined cultures. But it is necessary to emphasize forthwith that the circumstances of discovery are unfortunately not nearly so unequivocal that a discussion of the dating can be said to be superfluous. The Phaistos Disc was discovered in a narrow storeroom in a complex of dwelling-houses lying immediately north of the palace, and belonging to the earliest palace, which was destroyed in the period around 1700 BC (Pl. 1). But, as the following account of the excavation reports shows, the circumstances of discovery do not give the impression of any clear stratigraphy. In Pl. 1A the completely excavated row of houses can be seen; but when the disc was found only a corner of the western edge had been excavated, consisting of 8 small rectangular rooms, each with a breadth of about 80-115 cms. (Pl. IC). The first seven, which are about 130-150 cms. long, lie in a row, while the eighth, in which the Phaistos Disc lay, forms an independent wing at rightangles. The walls of the small rooms -probably storerooms, as they are too narrow for dwellings- are built on bedrock and survive to an average height of about a half metre. Rooms 1-7, and the southern two-thirds of room 8, were cleared during the campaigns of 1900 and 1903 (Pl. IB), and the clay disc was first discovered when the clearing of room 8 was completed in 1908. The room was thus unfortunately excavated in two stages. Luigi Pernier, who submitted the original excavation report, gives the following information concerning the details of the discovery of the disc ("Ausonia" III, 1908 p. 261): "A find of exceptional importance was made in the evening of the 3rd of July 1908. In the small rectangular room extending from the South wall of the cavities 6, 7 to the projecting rock, near the NW angle and ab. 55 cms. above the rocky surface of the bottom, among dark earth mixed up with ashes, charcoal and fragments of pottery, was found a disc of terracotta with pictographic signs on both faces. Few centimetres farther to the SE, in the same room, in practically the same height, lay a fragment of a clay tablet carrying characters of the Minoan linear script. The disc rested on a slanting surface (suolo di costa), not in a vertical position, but somewhat sloping northwards, showing on the upper side the face stamped in the centre with a rosette. Although the earth layer, upon which the disc was situated, was found to fill out irregular cavities in the bottom surface and between the stones projecting from the West wall, it did not seem to constitute a real floor-level, for the earth was not stamped compactly and contained, in the level of the disc as well as below it, pottery of the same sort and from the same period. Anyway it seems evident, considering the position in which it was found, that the disc was not in situ, but found presumably where it had fallen down from an upper storey, probably together with the tablet. It is worth while recalling the peculiar circumstance that one of our trial trenches in 1900 led to the discovery of room 8, leaving unexcavated only the small section in which were hidden the epigraphical documents. For this reason, mainly, it can be explained why it has not been possible to reconstruct any complete piece of pottery from the sherds found together with the disc." From the last remark it may be concluded that the potsherds found during the trial excavation in 1900 had been discarded or lost when in 1908 interest in them was aroused. It seems as though Pernier wished to keep open the possibility that at least a part of the objects found belonged to the original contents of the room. But opposed to this theory is his own observation that potsherds were found throughout the fill from the level of the disc and evenly down to the bedrock. It would be more reasonable to think of a gradual silting up, in association with the heaping up of refuse around the house ruins after their destruction, which appears to have been contemporary with the catastrophe which destroyed the first palace. The levels around the houses have proved to contain a number of potsherds from the whole of the Middle Minoan period, and it seems likely that in the period MM III they reached the top of the partially demolished walls and thereafter began to slide down and fill the "storerooms". Such a theory would also best explain the sloping surface (suolo di costa) on which the disc was found, cf. fig. 1. Pernier's information appears also to indicate that the MM III potsherds, on which the dating is based, lay in the disc's stratum and below, but not above. This fact alone seems to open the possibility that the disc did not belong to the level upon which it was found, but had been deposited upon it at a later date. Suspicion is strengthened when the following quotation from Pernier's report is read. It comes from immediately before the remarks already quoted concerning the finding-place of the disc. In a short survey of the objects discovered in the area in question Pernier describes under section 1 the ceramic material from the early Middle Minoan period, then proceeds to survey the objects from MM III, and inserts here as an introduction a paragraph which clearly is meant to convince the reader that, apart from a few "infiltrazioni" he is here describing a clear archeological horizon: "Finally in some of the rooms (in alcuni vani), in different levels, have been found some fragments of cups painted in Mycenean style and of pithoi with plastic decoration like those belonging to the late palace of Phaistos, but since these were mixed both with earlier sherds (Middle-Minoan) and with later fragments (Hellenistic), we are led to believe that in these places elements have intruded from the upper layers, of which in actual fact no other remains from the Late Minoan Period can be traced, except the abovementioned sherds." It would have been interesting to know in which of the rooms, and at precisely which height, the intrusive elements occurred, and in particular whether the phrase "alcuni vani" also includes room 8! To my enquiry whether the files of the Phaistos expedition might possibly contain further information about the circumstances of discovery, the present leader of the excavations, Professor Doro Levi, replied: "I am afraid that Pernier's excavation diary gives no more detailed report of the finding of the Phaistos disc than the accounts already published" (letter of 29. 3. 63), while no reply is yet forthcoming from Pernier's associate, Professor Luisa Banti. In the final excavation publication "Il Palazzo Minoico di Festos" I-II 1935-1951 reference is made to the preliminary report in "Ausonia", but it appears as though in the course of continued excavation in the area Pernier has somewhat changed his views. Vol. I p. 375 ends as follows: "Summing up the observations made of the ruins on the terrace northeast of the palace, it is evident that there were 4 edifices, connected with each other and dependent on the palace itself, though actually separated from it. Founded on an Early Minoan level they were probably erected as early as the beginning of the Middle Minoan period, and they were certainly used during MM II and III. The edifice in which the disc was found was abandoned after a catastrophe, the same, I think, which destroyed the palace in the last phase of MM. In the three other edifices, however (and especially the propylaea), the mixing up of Late Minoan I with earlier material seems to make it certain that, while the second palace was re-erected on a basis of the ruins of the first, the three buildings -and most clearly the propylaea-were still in use with slight modifications and additions. There arose then, on the ruins, during LM III some modest constructions (alcune modeste costruzioni), on which ultimately were built the houses of the Hellenic city." We seek in vain for documentation of the "modeste costruzioni" mentioned, and their modesty appears to be deduced from the fact that no material remains of them could be found at all, their existence being postulated on the basis of the discovery of Late Minoan potsherds. Pernier's phrasing in fact amounts to a re-evaluation of the "infiltrazioni" formerly so briefly dismissed, and this gives cause to inquire once more whether the level in which the Phaistos Disc was found is so certainly and unequivocally to be dated to MM III as is normally assumed. From the foregoing considerations it appears to me that categorical conclusions should be avoided, and that it should be assumed that the time of the deposition of the Phaistos Disc in the level in which it was found can lie anywhere at all between the end of MM III and the end of LM III, i. e. from about 1600 to about 1100 BC. This, of course, does not preclude that the disc is itself older than the date of its depositing. After its destruction at the end of MM III the palace was never re-erected as a unity, but several archeological observations show that Phaistos and the surrounding district continued to be thickly populated as long as to LM III. Luisa Banti states in the article on "Festo" in "Enciclopedia dell'Arte Antica" II (1960) p. 634: "The very abundant (abbondantissima) pottery from LM III has only been to a small degree published and studied". Cemeteries from this period have been discovered at Kalyvia near Phaistos. And after the destruction of the villa at Haghia Triada about 1400 new buildings were erected above and against the ruins of the villa, testifying to a cultural and material level still worthy of respect throughout LM III (cf. Luisa Banti's article on Haghia Triada in Enc. A.A. II 1087 seq.). Preliminary accounts of new discoveries of Mycenaean houses in Phaistos are given by Doro Levi in "III. London News" No. 6470 (3. 8. 63), p. 162 seq., in which Levi finds cause to emphasize that the Mycenaean period in Crete was not, as has always been claimed and frequently repeated, a period of decline, but on the contrary a rich and flourishing epoch. The current interpretation, in Levi's opinion, is connected with the contempt with which earlier excavators regarded all remains which were later than the Minoan civilization, then newly discovered. Levi emphasizes also the great difficulties, involving refined techniques of excavation, met with by modem excavators in clearly distinguishing between Minoan, Mycenaean and Hellenic strata. A greater uncertainty concerning the date of the Phaistos Disc is to a degree compensated for by a widening of the archeological horizon which can now be surveyed in an attempt to discover the milieu to which the disc belongs. If the disc was not made in Crete it may well have been imported from any area within the Mycenaean sea-trading area, in other words from practically the whole of the Mediterranean world. For Mycenaean pottery is found in many places outside the narrow Aegean area, not only on the Greek islands, in Cyprus, on the Syrian coast and in Egypt, but also far to the west, in Malta and Sicily and in South ltaly 3). It is probable that also the North African coast west of the Egyptian delta, at least as far as Syrte Minor, was reached by Mycenaean trading vessels, and it is tempting to accept the suggestion of H. C. Broholm, that Cyrene in the present-day Cyrenaica was founded as early as Mycenaean times, even though this theory has not yet been confirmed by the discovery of Mycenaean objects on the site 4). Any attempt to identify the homeland of the Phaistos Disc must be based on an analysis of the individual hieroglyphs. It must first be decided what the symbols actually portray (animals, plants, implements, etc.), and thereafter must be sought a closer identification zoological, botanical, cultural historical or art historical- which can help to narrow down the area of search 5). But first it will be practical to look at another side of the question, the place of the Phaistos Disc in the history of writing. I am grateful to the director of the Hiraklion Museum in Crete, Dr. Platon, for permission to study the original at close quarters. This enabled me in the first place to judge between the varying views which have been expressed concerning the direction in which the signs should be read. That the signs were impressed in the same order as that in which they should be read can scarcely be doubted, and it can with certainty be stated that the impressions were made in the direction from the circumference of the disc and in towards its centre 6). Certain groups of signs, where one sign overlaps the next, can appear from photographs to suggest the opposite order (fig. 2). But a closer examination shows that in all cases-on both sides of the disc -a sign which appears from photographs to overlap another has in fact been impressed before the second, but to such a depth that its impress could not be distorted or rubbed out to any appreciable degree by the next. The same conclusion is reached by study of signs which touch each other, for here the edges of the sign first impressed are normally slightly distorted 7). This observation agrees with the direction of the individual sign. Those signs which have a front and a back at all point in every case back towards the beginning of the inscription. This applies, for example, to all signs representing human beings, animals and fish, to parts of the body shown in profile and to certain other objects in profile, as for example the ship. An exception is perhaps the axe (sign 11), but the position of an axe is not absolutely fixed in relation to the vertical plane, and the specimen portrayed may well be an axe-adze, with two equally important blades. The other signs which can be roughly identified are all shown en face (all plants and trees for example), or can be turned either way without distinction. It should be noted, however, that the man -apparently literate- who impressed the signs has had no particular scruples with regard to the direction of the signs on the disc, but in many cases has turned them at will, either through mere thoughtlessness or in order to make room for a sign which took up too much room in breadth and had therefore to be stood on edge (for example the ship) 8). That there should be shortage of room is easily understood, as examination shows that the division of the spiral band by means of cross-lines into sections for each word was carried out before the signs were impressed, clearly in order to avoid the much more serious shortage of space which might arise if signs were merely impressed without previous planning, in succession towards the centre. Incidentally, this fact also shows that the inscription must have been copied from an earlier draft, as otherwise the rough division of the spiral band would have been impossible. This regularity in direction will in some cases be of help in identifying doubtful signs (cf. p. 185), and in addition shows that the script of the Phaistos Disc obeys at least one of the laws which apply to the ancient scripts of the Middle and Near East, that the individual sign can only be read in one direction. If the direction of writing changes, as in the archaic Greek "boustrophedon" inscriptions (alternately left-to-right and right-to-left), then the sign too must be written in the opposite direction. The direction of reading is thus hardly of great importance for the historical placing of an alphabet, or for estimating its relationship to other scripts. That the Phaistos Disc should be read from right to left does not therefore exclude the possibility of its being related to scripts which, like the Egyptian hieroglyphs or the Cretan linear scripts, are normally read from left to right. A separate analysis of the individual signs follows, general considerations being reserved to a final section. See Pls. II-III and VI-VII. Each sign is referred to by a number in brackets. (1) Human head, noticeably dolichocephalic and with long, thin neck. Eye, eyebrow and ear are clearly marked. The remarkable crest on the back of the head recalls a helmetcrest, but there is no sign of the accompanying helmet. The comparison suggested by Evans with the special headdress home by the Philistines on Egyptian battle-scenes of the 12th Century (Pl. II E) must be rejected. This headdress consisted (somewhat like that of the Indians) of a headband or diadem, to which was attached apparently a row of closely sitting vertical feathers or leaves. It appears to me that the crest in (1) cannot be interpreted as a headdress, but must be a special hair-style, as can still in our day be met with among certain primitive tribes 9). Egyptian monuments of the Second Millennium provide no parallels, but M-L. and H. Erlenmeyer have, in the article named in note 9, called attention to two terracotta heads (a. a. fig. 7-8, our Pl. II A) which undoubtedly resemble (1) closely. According to the dealer's information these heads were found on Crete together with a third head which is distinctly Philistine (a. a. fig.6). No conclusions concerning the origin of these specimens can be based on the place of finding. But it is of interest if they in fact were found on the same island, as it would in that case be reasonable to suppose that the people who fashioned the Phaistos Disc began to make themselves internationally known in the Mediterranean area about the same time as the Philistines, in LM III. To this can be added that Herodotus mentions and describes among the peculiarities of the Libyan nomad tribes between Egypt and Syrte Minor their remarkable hair-arrangement. Concerning the Maxyes tribe (presumably identical with the Mashawasha, a Libyan people mentioned in Egyptian victory inscriptions) he says that they let their hair grow on the right side of the head, but shave it off on the left (Her. IV 191). Two of the neighbouring tribes, the Machlyes and the Auseis, let their hair grow long on the front and the back of the head respectively (Her. IV 180). And finally the Makai tribe cut their hair in a crest, "allowing the middle part of the hair to grow, and shaving the hair on either side down to the scalp" (Her. IV 175). Here the word used is "lophos", which is normally employed in Greek of a horse's mane or a helmet crest, and it cannot be denied that this description suits (1) extremely well. Herodotus's description of the Libyan nomads is undoubtedly correct in all details, and it fits surprisingly accurately observations made by ethnographers among the present-day Tuareg (cf. Henri Lhote "Les Touaregs du Hoggar" 1955, p. 106 seq.). Among one of the southern tribes, the Timbuctoo people, the variations in hair-arrangement shown in Pl. II C are recorded 10). Hair styles of this type are occasionally seen on Egyptian monuments, as for example the Nubian on the Theban grave painting shown in Pl. III A. The resemblances between the ancient Libyans and the present-day Tuareg go, however, far over details of appearance, and witness to an unusual persistence in tradition during the 2400 years which have elapsed since Herodotus. There is therefore reason to believe that the situation described by Herodotus had not changed appreciably during the period of about 1000 years, which separates him from the heyday of Cretan culture. The hair-crest in (1) seems to be somewhat stylized; human hair is not normally so stiff unless it is treated in some way, but it is possible that the hair-style deliberately attempts to imitate an actual helmet crest 11). (2) Running man with dolichocephalic skull, cf. (1), bearing a loincloth and possibly, though not certainly, a phallos-sheath. The arms are only sketched, with no detail of the muscles, but the legs on the contrary are more detailed as to musculature, but oddly crippled, appearing to bend backwards. (3) Walking man, with dolichocephalic head, cf. (1) and (2). The arms are crossed behind the back, clearly bound. The position recalls Egyptian portrayals of captive foreigners. The front of the figure is not clearly impressed (the sign only occurring once on the disc). The legs resemble those of (2). There is no loincloth, but the projecting buttocks are clearly seen. (4) Female figure with long hair, stylized as in (1), bare torso with pointed pendular breasts, and a wide skirt in two pleats resembling closely the Minoan pleated skirt. A similar dress is, however, found on Syrian representations (Pl. II H) and is known in addition from the Western Mediterranean (Malta, Pl. II G). The face has a pointed nose, receeding chin and sloping forehead as in (1)-(3). The position of the arms, with the right arm hanging by the side, and the left crossing the breast, is parallelled often in the Mediterranean area 12). (5) The simple shape makes many interpretations possible, but the proposal of Evans, a woman's breast, seems the most plausible, cf. the Egyptian hieroglyph for "to suck" (Pl. II I). (6) Human figure of smaller size than (1) or (2), with round head, projecting arms and stomach, and bent legs resembling those of a child. The buttocks are prominent, though hardly to a degree that would suggest steatopygi. It is not impossible that the sign represents a pigmy, but the portrayal in fact suits better a child of a race of normal stature. (7) Hairless human head, definitely brachycephalic -as opposed to (1), (2) and (3)- and with low but definite forehead. Eye, eyebrow and ear portrayed as in (1). In addition there is on the cheek a mark in the form of two small circles, which must be interpreted as some form of painting or tattooing. This decorative element suggests that the intention is to portray a different population group than that shown in (1)-(4), and in that case the round head is hardly accidental, but rather a racial characteristic. The possibility may be considered that (1)-(4) represent a ruling class with more delicate features, while (7) shows an inferior element of the population with coarser lineaments. (8) It has been proposed to take this sign to represent a human hand wrapped in thongs of leather like those used by the pugilists of antiquity. However, it looks more like a modem boxing glove. It also bears a certain resemblance to a half-opened flower (like a rose), but again the bud is cut off rather abruptly and there is not even the suspicion of anything like a stem. On the other hand, if looked at from the opposite side, it seems to recall a piece of drapery, a skirt with folds of the type common in Ancient Egyptian art (Pl. II K-L) may perhaps be considered a precedent -the way of representing a piece of cloth exactly as it is usually worn, but without the human form filling it, is not quite so familiar that it would be superfluous to look for parallels 12a). In consideration of this precedent, however, the resemblance between (8) and the Egyptian figure illustrated in Pl. II D is certainly worth while considering. The loincloth worn by this figure, of fine linen, is of a special type, arranged on the front in a fanshaped series of pleats rather like an apron. In Egyptian art this sort of clothing is first represented about 1400 B.C., in the reign of Amenophis III, and it is still usual in the reign of Haremheb, during the transitional period between the 18th and 19th Dynasties. Non-Egyptian foreigners found this feature typically Egyptian, however, without understanding its functional idea. So, on a Syrian ivory from Ras Shamra, imitating Egyptian style, the pleated fan has been reduced to a small pendant-like palmette hanging down from the belt (PI. II F). As will be seen, (8) resembles the Egyptian prototypes more closely than the ivory, and moreover it is turned to the right like the other signs of the Phaistos Disc (cf. above p. 183). The interpretation proposed, therefore, is at any rate difficult to reject a priori. (9) Evans' comparison with the tiara-like Hittite head-dress is hardly convincing. Possibly the contours of the sign were not perfectly carved on the stamp (cf. (17)), so that the base line does not belong to the design proper. If so, the sign is actually of angular shape and bears a marked resemblance to the digging-stick used by the peasants of Ancient Egypt (Pl. III C) and still employed nowadays in many places in Africa for primitive agriculture. If this is true, the blade of the digging-stick is shown to the right, and the handle, in which it was inserted, to the left, which means that the tool is represented in working position, with the blade turned downwards. The sign therefore is turned correctly to the right. Possibly the base line discussed was intended to indicate the surface of the ground. (10) Provided that some object of daily use was meant (and not a mere signature, for example for mountains, huts or the like) it might be a pole (yoke) with two containers suspended, like the device carried by one of the women in the sacrificial procession on the well-known sarcophagus from Haghia Triada (Pl. III B, from ab. 1400 B.C.). (11) Axe with short, thin handle, presumably an axe-adze (cf. p. 183). This type is well known in the Aegaean from the early Middle-Minoan period (Pl. III H). (12) The sign represents an unstrung bow. The grip is marked. One of two different types may have been meant: either the bow is made of one single piece of wood like Egyptian bows from the Early Dynastic period (Pl. III F), or it is a composite bow reinforced by means of sinews (Pl. III D). The latter possibility seems more likely than the former. (13) Those who take this sign to represent a knife are probably right. Possibly, however, the knife is shown in its scabbard and this may be the reason only the tip of the handle is visible. This seems to be asymmetrically shaped, and the blade is very broad. The weapon therefore bears some resemblance to the typically Egyptian butcher's knife. (14) Object of lentoid shape provided with a loop or a handle, possibly a parrying shield like those still used by some African tribes (Pl. III G-1). (15) Possibly a rustic club, though the small knobs are placed at too regular intervals to conform to natural growth. More likely the club is studded with metal like those clubs used in time of Herodotus by the Ethiopians (Her. VII 69) and by the Assyrians (Her. VII 63). On the other band the sign might represent some kind of deciduous tree (e. g. poplar). (16) The short bar projecting from the centre may be a handle. The peculiar object was hardly intended to serve any practical purposes, but made rather for ceremonial use (thunderbolt?). (17) As often stated, there is an obvious likeness between the building type represented in this sign and the typically Lycian grave monuments of the Classical Epoch, which can hardly be quite fortuitous, though the Phaistos Disc belongs to a far earlier period. Similar edifices must have existed in Minoan Crete. The Cretan seal reproduced pl. VI C shows the upper floor with its steep gable and, below, a construction of poles raising the structure above ground level 13). The building represented in (17) was probably not circular in plan and not a dwelling house but presumably used for stores. The same main features (including a heavy ridge beam projecting from both gables) are reproduced in Minoan terracotta sarcophagi (Pl. VI B) and in one of the signs of the Mycenaean linear script B 14). Convex hip roofs were also known in Archaic Greece and must on the whole have had a wide geographical range 15). (18) Insect with small head, two forelegs, two wings and trace of abdomen, probably a bee. (19) Judging from the number, place, size and shape of the fins, the fish might be a species of mackerel (Bonito) or a herring- og mackerel-shark (Lamna nasus, Isurus oxyrrhynchus), but the pointed shape of the head does not fit this theory 16). A precise zoological definition. is difficult to formulate, but probably not because the species in question is a very rare one. More likely the distinctive features are not correctly rendered in every respect. Of these the shape of the head is by far the most peculiar, and is, as it seems, more compatible with the forepart of the dolphin than with any species of fish. The foremost abdominal fin, too, resembles rather closely the flippers of the dolphin, and the dolphin has also a dorsal fin like the foremost one on the sign. The tail, however, seems to have been copied from a fish. Some representations of dolphin on Mycenaean vases (Pl. VII B) show the same confusion of ideas 17), whereas those in, and those inspired by, Minoan art are much more true to nature (Pl. VII C-D). (20) No doubt represents a ship, and vessels of this design are known from Cretan seals (Pl. VI D-E), apart from the form of the prow, which is somewhat different. The prow is distinguished by the projecting keel. The sign, therefore, is turned correctly to the right like the other profile signs. (21) Wavy symbol, representing presumably "water" or "sea". (22) The shape may resemble that of a three-pronged harpoon, but there are no barbs. Other possibilities: a hay-fork like that used in Ancient Egypt (Pl. VII A), or perhaps a somewhat schematic lotus flower. (23) Umbelliferous plant. The small leaves projecting at regular intervals from the vertical stem seem to be the most distinctive feature, but from a botanical point of view they are hardly conclusive. Probably (as in the case of (19)) the design stands for a well-known species, and it is not less compatible with the true appearance of the papyrus than the majority of the ornamental imitations in Egyptian art and in the Aegaean trends influenced by Egyptian style (Minoan and Mycenaean, Pl. VII I). The papyrus stalk has in actual fact no leaves, but Nature was not always correctly copied even in Egyptian art (Pl. VII H)18). (24) Ox horn. (25) Hoof, presumably of an ox. (26) A distended animal's skin, probably of ox or sheep. The line of the spine is marked with a fine groove (clearly visible in Evans, Scripta Minoa I pl. XII)19). (27) Head of ram, possibly wild sheep (mouflon). (28) Cat's head. The style is markedly Egyptian (cf. Pl. VII E, G) and the head is possibly copied from an Egyptian drawing, perhaps a papyrus with representations of fables of animal life 20). (29) Bird of prey with extended wings clasping with its claws a nondescript round object, possibly a symbol of some sort like those carried by the vulture-god Nekhbet or the Horusfalcon in Egyptian art (Pl. VII F). (30) Seated bird with long flight-feathers, possibly a dove. (31) Branch with 5 leaves of trilobate outline. A vine? (32) Low crooked deciduous tree like olive or fig. (33) The sign could be taken to represent an arrow (cf. the bow (12)) equipped with flight feathers, but there is no indication of a point or of any thickening that might suggest the presence of a transverse arrowhead. I am inclined to believe therefore that the object reproduced is rather an ear of corn with long "whiskers" 21), that is, presumably, some species of barley. The remaining signs 34--45 are especially enigmatic, either because their shape is very schematic and simplified, or because the objects represented were not universally used in the Mediterranean area. At any rate, (45) is certainly not a libation jug of Minoan shape, as suggested by Evans, for the handle is not separately marked, and the hatching fills out completely the outline of the sign. As already stated, the conventional dating of the Phaistos Disc, though based on excavation reports, is by no means susceptible of proof. The fill in which the disc was found was not so clearly stratified that a chronological sequence could be established beyond doubt. In view of this conclusion, therefore, it does not appear a priori absurd, that some of the signs seem to recall stylistical features characteristic of a period definitely later than the epoch to which the disc is usually assigned. The Phaistos Disc is certainly a uniform piece of workmanship, and all signs resemble each other in the general characteristics of their style. Nonetheless, some of them bear a certain resemblance to conventional Egyptian design. This is particularly true of the cat's head (28), and one is tempted therefore to keep on the look-out for similar cases. Another case, especially worth of consideration, is (8). Mention has already been made of two types of loin-cloth common in the old kingdom (fig. 3). One of them (fig. 3 A, Pl. II K-L) is reproduced in practically the same way in later periods. The other one, the typical feature of which is the fold-fan radiating from the front side of the waist, is represented in a greatly stylized manner in the art of the Old Kingdom, but in the later part of the 18th Dynasty a more naturalistic way of rendering the folds becomes fashionable (PI. II D) 22). If it is true, therefore, that this fashion is imitated on (8), the Phaistos Disc cannot be earlier than about 1400 B. C. If (14) represents, in actual fact, a parrying shield (a possibility suggested above), this feature may also indicate a date later than ca. 1400 B. C. Parrying shields were known in Egypt at a much earlier date, but they were not commonly used in the Near East until the last centuries of the second Millennium, when the slashing sword became preponderant in warfare (cf. R. W. Hutchinson, Prehistoric Crete (1962) p. 253). Among other signs possibly betraying Egyptian influence may be mentioned (1), (2) and (3). Provided that the markedly dolichocephalic shape of the human heads in these signs, particularly in (1), is not an ethnic feature, it may have been copied from Egyptian art. As is well known, the heretic king Amenophis IV (Echnaton) possessed a skull of an abnormally elongated form, and in the royal art encouraged by the monarch himself this peculiar feature was canonized as a standard of beauty. Not merely the royal family, but persons of lower rank as well, were represented with skulls of royal proportions, and this habit seems to have prevailed until some time after the death of Echnaton in 1352. The physical appearance of the king was also peculiar in other respects: he had a long, thin neck and a body of feminine curves with a narrow waist, swelling hips and slim girlish legs (Pl. II B). These characteristics are openly portrayed: evidently this was the appearance which the king wanted to exhibit in public and which was known in foreign countries and admired by less civilized peoples. The frail and crooked legs of the human figures on the Phaistos disc, (2) and (3), may therefore also have been imitated from Egyptian models. Finally it should be mentioned that the typically Egyptian plants, the papyrus and the lotus, are possibly represented in (22) and (23). It thus seems that the Phaistos Disc was fashioned in a district submitted to a certain degree of Egyptian influence. This Utopia, which we may provisionally call the unknown area in question, was no doubt situated somewhere along the Mediterranean coastline (judging from the ship (20) and the dolphin (19)), and the place of discovering of the disc suggests that maritime connections existed between Utopia and Crete. As we have seen above, (1) may point to an African origin. According to (24)-(27), oxen and possibly sheep or goats formed part of the economy of Utopia; (28) suggests that the cat was kept as a domesticated animal; and judging from (32) and (33) corn was grown and the climate was suitable for deciduoustrees, while, according to (17) timber was used freely in house-building. Would these specifications conform to climatic conditions along the coast of North Africa in the 14th century B. C.? Not much is actually known as regards this subject, except what can be deduced from Herodotus. The Libyan tribes were, in the eyes of Herodotus "nomads", and the country on the whole of no great value. However, a few exceptions are mentioned, like the land of the Makai (cf. commentary to (1)). This district was watered by the river Cinyps, corn of the best quality was grown, and the area was also very unlike most of Libya in other respects. "The earth is dark and is kept moist by springs, and the heat is not to be feared ... in quantity the harvest compares with the yield of Babylonia" (Her. IV 198). The other notable exception was the coastal regions of Cyrenaica, which, however, was not so fertile as the Cinyps valley. The nomads, says Herodotus, live in huts plaited of rush and stems of plants, but farther west, beyond the Triton river near the Syrte Minor, the tribe called Maxyes are settlers living in real houses (Her. IV 191), and the area still farther west is even more woody than Eastern Libya. It is open to doubt whether conditions had changed notably in the course of the thousand years preceding the time of Herodotus, in any event they had hardly improved. Presumably the gradual desiccation of North Africa, the result of which in a still more remote period was the isolation of the Nile valley, continued right down to the Classical Era, and conditions may have been rather more favourable at the time of the Phaistos disc than in the days of Herodotus. In favour of a North African origin of the disc it may be argued, also, that this region is not so well explored (apart from Phoenician, Greek and Roman settlements) as the East Mediterranean countries. Other inscriptions in the alphabet of the Phaistos Disc are therefore more likely to be found in the west. There are no indications suggesting that any Aegaean commumties, apart from Crete and Mycenaean Greece, had alphabets of their own. Troy, the most important city of Western Asia Minor, had none, and prosperous Cyprus managed with an adaptation of the Mycenaean linear script. It is not likely therefore that settlements along the rocky shores of Southern Asia Minor would have taken the trouble to invent new types of script. Excepting adaptations of Babylonian cuneiform script (Hittite, Ugaritic), the earliest local alphabets are found in the commercial centres along the Syrian coast. But these have nothing in common with the script of the Phaistos disc. Of communities sufficiently organized in economical and political respects to feel the need of a script there remained presumably, then, only those situated immediately to the west of Egypt. From the 14th century onwards the peoples of these regions are recorded in history as dangerous enemies, attacking repeatedly the Egyptians in the rear and checking together with Philistines and other "Peoples of the Sea" Egyptian expansion towards the north. For the present the use of phallus-sheaths in Crete seems to be the best argument that can be adduced in support of very old connections between North Africa and Crete. Since very little is known of Libya in the Bronze Age, it is difficult to measure the frequency of contact with Minoan Crete in this epoch 23). It should be noted, however, that in the Greek period Cyrenaica was colonized from the nearest Greek islands, Crete and Thera, and it seems probable that the creation of the Roman province Creta et Cyrenaica was a practical confirmation of a traditional intercourse. Whatever the exact location of Utopia -if it is true that the Phaistos Disc belongs to the 14th century, it can under no circumstances have been fashioned in Crete. By this period hieroglyphic script in Crete had been definitely abandoned in favour of linear scripts, and the crude signs of the disc would certainly not compare with the subtleties of Late Minoan art. Kristian Jeppesen